2002
DOI: 10.3732/ajb.89.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Host compatibility of the cloud forest mistletoe Psittacanthus schiedeanus (Loranthaceae) in Central Veracruz, Mexico

Abstract: The consequences of the seed deposition of the parasitic mistletoe Psittacanthus schiedeanus were evaluated in a 32-mo study. We conducted a field seed inoculation experiment to determine variation in seed adhesion, seed germination, seedling establishment, and plant survival to reproduction among five host species and to evaluate whether these post-dispersal processes explain mistletoe prevalence and specificity at the regional scale. Seeds without an exocarp were inoculated onto branches of individuals of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Some dwarf mistletoes are so host specific that it has been suggested that their host specificity may be a useful taxonomic character for distinguishing between host populations (87,137). Although host specificity is commonly mentioned in the mistletoe literature, and many authors have pointed to its importance to pathology, few investigations have examined the mechanisms that control mistletoe-host compatibility (7,50,100,157,188,208,227,228,229). A better understanding of the mechanisms related to host specificity would have applications to mistletoe control, particularly in developing greater host resistance (196).…”
Section: Mistletoes As Pathogensmentioning
confidence: 99%
“…Some dwarf mistletoes are so host specific that it has been suggested that their host specificity may be a useful taxonomic character for distinguishing between host populations (87,137). Although host specificity is commonly mentioned in the mistletoe literature, and many authors have pointed to its importance to pathology, few investigations have examined the mechanisms that control mistletoe-host compatibility (7,50,100,157,188,208,227,228,229). A better understanding of the mechanisms related to host specificity would have applications to mistletoe control, particularly in developing greater host resistance (196).…”
Section: Mistletoes As Pathogensmentioning
confidence: 99%
“…The existence of host-specific relationships through cross-dispersal experiments has been suggested as evidence for the presence of host-specific races in a number of mistletoe species (e.g., [ 15 21 ]), or by using genetic markers, including isozymes [ 22 26 ], AFLPs [ 27 ] and chloroplast DNA sequences [ 6 , 7 , 28 , 29 ]. Cross-dispersal experiments have shown that seedling development is greatest when mistletoe seeds are placed on their source host species [ 15 17 , 20 , 21 , 30 , 31 ]. Using genetic data, however, the distinct host races identified were geographically isolated by some distance (except [ 25 , 26 ]) or the phylogeographic groups were best explained by isolation linked to Pliocene geological events and Pleistocene climate changes [ 6 , 7 ], which makes it difficult to distinguish between the potential effects of isolation and those linked to changes in host-tree availability on population divergence.…”
Section: Introductionmentioning
confidence: 99%
“…& Schlecht.) G. Don is characteristic of the canopy in the cloud forest edges in Mesoamerica and often parasitizes tall trees ( López de Buen and Ornelas, 2002 ). The hermaphroditic, hummingbird-pollinated flowers are self-compatible ( Ramírez and Ornelas, 2010 ), and ripe, lipid-rich, purplish-black fleshy fruits are dispersed by a variety of resident and migratory bird species ( López de Buen and Ornelas, 1999 , 2001 ; Ramírez and Ornelas, 2009 ).…”
mentioning
confidence: 99%